Incidence of Smartphone in the development of brain plasticity in children from 0 to 6 years old, in a context of high vulnerability - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2020)
The research project that presents a complete update for a systematic review regarding the use of smartphones. The development of cerebral plasticity in children aged between 0 and 6 years. This review is composed of three complete categories of content: Intellectual, attitudinal and behavioral, all definitions are made up of a certain number of Skills, which are expressed in the various systematic versions, including gray literature, which will provide the basis and theoretical foundations and practical ones that allow the deduction of new investigations